Dundai Naek Sialang Sebagai Warisan Budaya Takbenda: Tradisi Lisan, Kearifan Lokal, dan Perspektif Ekoteologi Islam Dalam Pelestarian Hutan di Musi Banyuasin - Wanda Lesmana; Andy Hariyono; Puji Eko Purnomo; Herwandi; Munir (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study explores the oral tradition of Dundai Naek Sialang in Musi Banyuasin Regency, South Sumatra, as a form of local wisdom in traditional honey harvesting that preserves ecological balance. Using a descriptive qualitative method with ethnographic approaches—field observation, interviews with cultural maestros, and documentation of chants and practices—the research interprets symbolic meanings, cultural values, and ecological wisdom. Complementary analysis of Qur’anic exegesis, particularly Rūḥ al-Ma‘ānī by Al-Ālūsī, through Qawā‘id al-Tafsīr and Maqāṣid al-Syarī‘ah, situates the tradition within Islamic ecotheology. Findings reveal that Dundai Naek Sialang is not merely ritual chanting but embodies spiritual, social, and character education values aligned with Qur’anic messages on human stewardship (khalīfah, QS 2:30), prohibition of corruption (fasād, QS 7:56), and cosmic trust (amanah, QS 33:72). Thus, the tradition is relevant as intangible cultural heritage and ecological worship practice.